PENGARUH DISIPLIN KERJA DAN KOMUNIKASI DALAM ORGANISASI TERHADAP KINERJA PEGAWAI (Studi Pada Dinas Pariwisata dan Kebudayaan Kota Batu) - Melia Excelsa (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to determine the effect of work discipline and organizational communication on performance of employees in Departement of Tourism and Culture of Batu. The instruments of this study were assessed using validity and reability test. The analytical tools are descriptive analysis  and  multiple linear regression analysis.This study was conducted on 60 employees of Departement of Tourism and Culture of Batu. The results of this research is that work dicipline has no significant effect on employee performance, but organizational communication has a significant effect on employess performance. The result of the analysis shows that employee performance is influenced by work discipline and communication in the organization. Pther factors that are suspected to infuence employee performance are motivation, leadership style, and organizational culture.Keyword: work discipline, comminication in the organization, employee performance